2012
DOI: 10.1038/clpt.2012.73
|View full text |Cite
|
Sign up to set email alerts
|

Drug Absorption Interactions Between Oral Targeted Anticancer Agents and PPIs: Is pH-Dependent Solubility the Achilles Heel of Targeted Therapy?

Abstract: A majority of the novel orally administered, molecularly targeted anticancer therapies are weak bases that exhibit pH-dependent solubility, and suppression of gastric acidity with acid-reducing agents could impair their absorption. In addition, a majority of cancer patients frequently take acid-reducing agents to alleviate symptoms of gastroesophageal reflux disease, thereby raising the potential for a common but underappreciated drug-drug interaction (DDI) that could decrease the exposure of anticancer medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
302
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(311 citation statements)
references
References 29 publications
2
302
0
2
Order By: Relevance
“…The measured solubility and dissolution properties of LY3023414 were favorable for absorption if compared with published data for other PI3K/mTOR inhibitors (2,30,43). The compound was quite soluble near pH 2, which corresponds to the initial pH encountered by LY3023414 in the stomach, and remained soluble in simulated gastric and intestinal fluids.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The measured solubility and dissolution properties of LY3023414 were favorable for absorption if compared with published data for other PI3K/mTOR inhibitors (2,30,43). The compound was quite soluble near pH 2, which corresponds to the initial pH encountered by LY3023414 in the stomach, and remained soluble in simulated gastric and intestinal fluids.…”
Section: Discussionmentioning
confidence: 79%
“…The compound was quite soluble near pH 2, which corresponds to the initial pH encountered by LY3023414 in the stomach, and remained soluble in simulated gastric and intestinal fluids. The favorable solubility of LY3023414 between pH 4.5 and pH 7.5 is expected to minimize precipitation that can contribute to variable and lower absorption in the intestinal tract (29,30). Modeling in a gastroduodenal passage model indicated that absorption would be only slightly reduced by coadministration of gastric pH-altering proton-pump inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These bind irreversibly to hydrogen potassium ATPase pumps and may elevate gastric luminal pH to as high as pH 7. 125 The duration of PPI-induced gastric acid suppression [125][126][127][128] may potentially be sustained for several days after therapy cessation. 129 Coadministration of an acid-reducing agent may markedly impair systemic absorption of many of the molecularly targeted agents (which exhibit pHdependent solubility), 128 potentially causing suboptimal tumor exposure and development of drug resistance pathways.…”
Section: Comedication Usementioning
confidence: 99%
“…125 The duration of PPI-induced gastric acid suppression [125][126][127][128] may potentially be sustained for several days after therapy cessation. 129 Coadministration of an acid-reducing agent may markedly impair systemic absorption of many of the molecularly targeted agents (which exhibit pHdependent solubility), 128 potentially causing suboptimal tumor exposure and development of drug resistance pathways. 124,[130][131][132][133] This mechanism, from one class alone of drugs commonly coadministered with oral TKIs, adds further concerns to a dosing regimen of "one dose fits all" with oral TKIs.…”
Section: Comedication Usementioning
confidence: 99%